Head and neck radiology - Mancuso, Anthony A. (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2011)
"Written and edited by acknowledged masters in the field, this two-volume full-color text is the most comprehensive and current reference on head and neck radiology. It features more than 10,000 images and covers every disorder in every region of the head and neck. The first two sections cover applied imaging fundamentals and general pathology, pathophysiology, patterns of disease, and natural history of head and neck disorders correlated with imaging appearance. Subsequent sections focus on specific anatomic regions: the eye, orbit, visual pathways, and cranial nerves III, IV, and VI; sinonasal and craniofacial region including cranial nerve V; temporal bone, posterior skull base, posterior fossa, and cranial nerves VII-XII; infrahyoid neck and cervico-thoracic junction (thoracic inlet); thyroid and parathyroid glands; major salivary glands; nasopharynx; oropharynx; oral cavity and floor of the mouth; larynx, hypopharynx, and cervical esophagus; trachea; hypopharynx; and cervical esophagus. The text covers all current imaging modalities, including plain film, MRI, CT, ultrasound, and nuclear medicine including PET. A companion website will offer the fully searchable text and images. The first two sections will be online only. The website will also include imaging protocols and bonus cases"--Provided by publisher.